Integrative analysis of microRNAs and mRNAs involved in regulation of intramuscular fat deposition in Nelore cattle - Oliveira, Gabriella Borba de (2017)
The amount of intramuscular fat can influence the sensory characteristics and nutritional value of beef, thus the selection of animals with adequate fat content for consumer becomes important. Intramuscular fat is a complex trait that is difficult to measure and there is growing knowledge about the genes and pathways that control the biological processes involved in fat deposition in muscle. MicroRNAs (miRNAs) are well conserved class of non-coding small RNAs that modulate gene expression of a range of functions in animal development and physiology. This study aimed to identify differentially expressed (DE) miRNAs, regulatory candidate genes and co-expression networks using mRNAs and miRNAs expression data from the Longissimus dorsi muscle of 30 Nelore steers with extreme genomic estimated breeding values (GEBV) for intramuscular fat (IMF) content. The differential expression analysis between the miRNA data from animals with extreme GEBV values for IMF identified six DE miRNAs. Functional annotation of target genes for these microRNAs indicates that PPARs signaling pathway is involved with IMF deposition. Regulatory candidate genes such as SDHAF4, FBXO17, ALDOA and PKM were identified by partial correlation with information theory (PCIT), phenotypic impact factor (PIF) and regulatory impact factor (RIF) approaches from integrated miRNAs-mRNAs expression data. Two DE miRNAs, bta-miR-143 and bta-miR-146b, upregulated in Low IMF group, were also correlated with regulatory candidate genes, which were functionally enriched for GO terms for fatty acids oxidation. Co-expression networks identified several modules related to immune system, protein metabolism, energy metabolism and glucose catabolism by weighted correlation network analysis (WGCNA), which showed possible interaction and regulation between mRNAs and miRNAs. This study contributes to our understanding of regulatory mechanisms of gene signaling networks involved in fat deposition process. Glucose metabolism and inflammation process were the main pathways found in integrative mRNAs-miRNAs analysis and showed to influence intramuscular fat content in beef cattle.